Bioactivity of Bee Venom on European Foul – Brood Bacteria - Al- Zubadi, A.N. Oueed; Al- Musafer, M. A. Kareem; Al-Jorany, R S . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Laboratory experiments were carried  out in Technical college AL- Mussiab / Babylon during 2005  to study bioactivity of different concentration from ( aqueous , alcohol and hexane) extracts of bee venom collected from different workers of bees against some bacterial types that cause European Foul â€“ brood Melissococcus plutom , Bacillus alvei and B. letrosporus which had been isolated from infected arched with disease . Two diffusion methods (digging and paper discs) were followed for the extraction of the venom . Results showed that digging diffusion method was more efficient for  test of bacterial inhibition which led to increase the activity of bee venom extract with general average 7.90 , 8.85 and 8.19  on M. pluton, B. alvei and B. letrosporus. Alcoholic bee venom extract showed high efficiency in inhibition for the same bacterial species above by digging method too with diameters average 8.15 ,9.76 and 10.59 mm respectively . while aqueous extract was the less efficient in bacterial growth of these bacterial species that reached 7.26 , 7.70 and 6.26 mm respectively in paper discs method  compared with control 6.00 mm. On the other hand 40% concentration of bee venom showed high effect of bacterial growth for  M.pluton , B. alvei and B. letrosporus with averages 10.60 , 15.60 and 15.60 mm respectively while 1% concentration had no effect in growth of these bacteria compared with control treatment 6.00 mm .Ther is an interaction between the diffusion method, concentration and the kind of the extract . The results reflected that Alcoholic extract at 40% con. by digging method gave a higher inhibition of growth 10.60 , 15.60 and 15.60 mm in M. pluton , B. alvei and B. letrosporus respectively.  40% con. of bee venom compounds however was more effective for bacterial species compared with Oxytetracyclin antibiotic that was very effective in B. alvei  and B. letrosporus and less effective in M. pluton bacteria .